Influence of kinetic and thermodynamic promoters on post-combustion carbon dioxide capture through gas hydrate crystallization - Kumar, A.; Bhattacharjee, G.; Barmecha, V.; Diwan, S.; Kushwaha, O. S. (Journal of environmental chemical engineering, 2016)
In the present work, we report enhanced kinetics of hydrate formation in the presence of kinetic and thermodynamic promoters, SDS (sodium dodecyl sulphate) and THF (tetrahydrofuran) respectively. Hydrate formation was carried out in a fixed bed reactor for post-combustion capture of CO2. Silica sand was used as a fixed bed medium to capture CO2 from a CO2/N2/SO2 (17.7 mol% CO2, 1.05 mol% SO2 and balance N2) gas mixture by hydrate crystallisation. Experiments were performed at a constant temperature (273.65 K) and at different pressures (9.5 and 2.45 MPa) in batch mode. It was found that the addition of SDS enhances the rate and gas uptake of gas hydrate formation. A higher gas consumption was achieved by using 5.56 mol% THF compared to 1.0 and 3.0 mol% THF.

An innovative approach to enhance methane hydrate formation kinetics with leucine for energy storage application - Veluswamy, H. P.; Kumar, A.; Kumar, R.; Linga, P. (Applied Energy, 2017)
Natural gas storage in dathrate hydrates or solidified natural gas (SNG) offers the safest, cleanest and the most compact mode of storage aided by the relative ease in natural gas (NG) recovery with minimal cost compared to known conventional methods of NG storage. The stochastic nature of hydrate nucleation and the slow kinetics of hydrate growth are major challenges that needs to be addressed on the SNG production side. A deterministic and fast nucleation coupled with rapid crystallization kinetics would empower this beneficial technology for commercial application. We propose a hybrid combinatorial approach of methane hydrate formation utilizing the beneficial aspect of environmentally benign amino acid (leucine) as a kinetic promoter by combining stirred and unstirred reactor operation. This hybrid approach is simple, can easily be implemented and scaled-up to develop an economical SNG technology for efficient storage of natural gas on a large scale. Added benefits include the minimal energy requirement during hydrate growth resulting in overall cost reduction for SNG technology.